Концептуальні домінанти мовосвіту Олеся Гончара - Сніжко, Н. (Культура слова, 2018)
Стаття присвячена аналізу концептуальної картини світу Олеся Гончара, яка є важливим складником сучасного українського мовомислення. У творчій спадщині письменника представлені константи української та світової культури, які увиразнюють традиції світосприймання, а також нові концептуальні домінанти, що відтворюють оновлене українське світобачення, утверджують процеси демократизації та гуманізації суспільства. Багатий неолексикон та оригінальна образна система Олеся Гончара – вдячний фактичний матеріал для сучасних досліджень неології, лінгвокогнітології, лінгвоконцептології, лінгвокультурології, лінгвостилістики та авторської лексикографії. The article is devoted to analysis of the conceptual picture of the world by Oles Honchar which is the basis for the development of modern Ukrainian language thinking, the development of Ukrainian linguistics and the establishment of the state of Ukraine. In the creative heritage of the writer, the constants of Ukrainian and world culture are presented, which reveal the traditions of worldview, as well as new conceptual dominants that reproduce the updated Ukrainian worldview, establish the processes of democratization and humanization of society. The rich neo-lexicon of Oles Honchar and his original conceptual image system reinforce contemporary macro-scientific research and provide understanding of the theoretical foundations of neology, linguocognitology, and linguoconceptology, and linguoculturology, linguostylictics and authorʼs lexicography.